“ARRANGED MARRIED” DALAM BUDAYA PATRIARKHI (Studi Kasus Komunikasi Budaya Pada Pernikahan Di Desa Ambunten, Kabupaten Sumenep) - Rivial Haq Arroisi; Dewi Quraisyin (Jurnal Komunikasi, 2015)
This research titled “Arranged Marriage” In Patriarchal Culture, the purpose of this research was to determine how “Arranged Marriage” in the patriarchal culture in Madura, Arranged Marriage is a marriage which arranged, where the role of a father who set up a child’s life, with whom she will marry, when she will get married, how she will living her life and where she will stay after marriage, it makes as if a child do not have freedom in choosing a life partner, this case is for real, and this phenomenon occurs in Madura.This research was descriptive qualitative. Primary and secondary data derived from interviews, documentation, and literature. The subject of this study is the informant of Mr. Multasim Syuro family, Mrs. Nurmut Mainah, Mr. Safrawi, Mrs. Ruhani, and additional informant Mr. Muhammad Munir. While the object is the Arranged Marriage. In order to test the validity of the data, we use triangulation of source.Based on the above methods, it was found that patriarchy is a culture that has existed since long ago, where men hold power over all important role of society, both in government, education, industry, business, health care, and within the scope of the family will result in the loss of the role of a woman from access to that power. the role of a father in the family to set up a child’s life, starting to whom she will be marry, when to marry, and how she living after marriage. With the father’s role as the person who hold the top notch in the household, the desire of a father to marry off their children with relatives, friends, or colleagues, it is intended that property owned not fall into the hands of others.Keywords : Cultural communication, Arranged Marriage, Patriarchy culture